THEORETICAL ISSUES OF A PUBLIC-LEGAL DISPUTE CONCEPT IN THE PROCESS FOR APPEALS AGAINST DECISIONS OF COMPETITIVE SELECTION COMMISSIONS OF ECONOMIC ENTITIES’ HEADS IN THE STATE SECTOR OF ECONOMY - Ustynova, Iryna P.; Husar, Olga A.; Myronets, Oksana M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to investigate the current mechanism for appeals against the decision of the competitive selection commissions of economic entities’ heads in the state sector of economy as a type of a public-legal dispute and to express an opinion on the regulation of these relations in Ukraine. Research methods: general-scientific and special-legal methods of scientific knowledge, in particular: system-structural and functional methods, method of observation, method of generalization, methods of analysis and synthesis have been applied. Results: the current normative regulation of the procedure for appeals against the decision of the competitive selection commissions of economic entities’ heads in the state sector of economy as a type of a public-legal dispute has been analyzed and the judicial practice has been assessed. Discussion: there is a significant lack of scientific research on appeals against the decision of the competitive selection commissions of economic entities’ heads in the state sector of economy as a type of a public-legal dispute. This issue has not been considered in many aspects, and various objective indicators have not been taken into account, so the level of research on the theme is low. This is due to the novelty of this theme, as appeals against the decisions of competitive commissions in the public (administrative) process are from the beginning of 2020. Previously, this type of relations was considered only in the context of civil law.